Physicochemical Properties of Pempek Made with Snakehead Fish (Ophiocephalus striatus) Premix Flour - Safarni, Rizka Aulia; Tawali, Abu Bakar; Abdullah, Nurlaila (Jurnal Biologi Tropis, 2025)
Snakehead fish (Ophiocephalus striatus) contains high-quality protein (25.1%) and albumin (6.224%), which supports cell and tissue regeneration. However, its snake-like appearance reduces consumer appeal. This study aimed to determine the optimal formulation of premix flour for pempek production with snakehead fish flour and to evaluate its nutritional content. The research involved five stages: production of fish flour, formulation of premix flour, pempek preparation, organoleptic testing using the hedonic method, and proximate analysis. A total of 15 treatment combinations were tested with four levels of fish flour substitution (10%, 20%, 30%, 40%). The best formulation, based on organoleptic parameters (taste, aroma, texture, color), was 40% snakehead fish flour, 29.2% tapioca flour, 29.2% sago flour, and 1.6% seasoning. Nutritional analysis of pempek from this formulation showed a moisture content of 36.65%, ash 2.08%, protein 24.64%, fat 5.47%, and carbohydrate 31.17%. This study concludes that snakehead fish flour can be effectively used in pempek production to enhance its protein content and nutritional value while maintaining acceptable sensory characteristics.